МАТЕМАТИЧНЕ МОДЕЛЮВАННЯ ВПЛИВУ ОПРОМІНЕННЯ НА ПРОДУКТИВНІСТЬ ПРОЦЕСУ ВИРОЩУВАННЯ РОСЛИННОЇ ПРОДУКЦІЇ В ГІДРОПОННІЙ УСТАНОВЦІ - KUPCHUK , IHOR; MELNYK, OLEXANDER (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The actual problems of agriculture not only in Ukraine but also in other countries are to increase crop yields, increase nutritional value, quality and reduce production costs, reduce the required production area, the cost of agricultural machinery, etc. In this regard, hydroponic plants look quite promising, as they provide round-the-clock cultivation of a wide range of crops with minimal space, capital and operating costs, and a halved harvest period. The widespread introduction of hydroponic equipment and technology in Ukraine will allow for the fullest realization of the concept of small enterprises, which in this case can be created with little or no start-up capital. In addition, the use of hydroponics will allow existing enterprises of various profiles and small farms to receive additional income or valuable plant material.Hydroponics is a promising area of modern agriculture that ensures long-term cultivation of the main types of vegetables and greenery in small areas with minimal water and fertilizer consumption. This technology allows you to get a fairly large harvest of fresh vegetables within large cities, including office and residential premises. The main trends in improving this technology are expanding the range of crops grown, their yields, more efficient use of land, soil, nutrients, minerals, water, energy, and reducing the cost of finished products.. The article is devoted to the development and study of a mathematical model of the influence of irradiation on the productivity and quality of hydroponically grown products. In particular, dependencies were obtained to determine the influence of irradiation parameters on the development of lettuce, the use of which allows predicting the size and weight of the plant, forming the basis for optimizing the operating parameters of the hydroponic plant.
Keywords: artificial lighting; photosynthetic active radiation; vegetation; photosynthesis; nutrition